Primary Yolk Sac Tumor of the Liver in an Adult Man. Issue 4 (April 2019) - Vanidassane, Ilavarasi; Sharma, Vinod; Ramteke, Prashant; Yadav, Mukesh Kumar; Batra, Atul
Abstract : ABSTRACT: Primary yolk sac tumor of the liver is extremely rare in adults. We report a case of a young man with an unresectable primary yolk sac tumor of the liver, who had a platinum-refractory disease that progressed despite 2 lines of chemotherapy. We review the literature pertaining to primary yolk sac tumor of the liver and its management.